Enhanced Chaos Generation in Mid-Infrared Interband Cascade Lasers Under Amplitude-Modulated Optical Injection - Hong Han; Jiada Xu; Zhiwei Jia; Jianguo Zhang; Mingming Huo; K. Alan Shore (Photonics)
We numerically investigate the dynamics of an interband cascade laser (ICL) subjected to amplitude-modulated optical injection from a directly modulated master ICL. In comparison with steady-state optical injection, the proposed modulated optical injection significantly enlarges the chaos region. In excess of 10 GHz broadband mid-infrared chaos is obtained at large bias currents and with a high gain stage number for the appropriate choice of master-slave detuning, modulation frequency, and modulation depth.